Designing the Structural Model of TVET Lecturers’ Professionalism and Generic Skills Based on an Empirical Study in Malaysia - Abdullah, Zuraidah; Hoque, Kazi Enamul; Ramlan, Nor Hayati; Shafee, Salwati (SAGE Publications, 2019)
This study seeks to identify the level of general competency of technical and vocational education and training (TVET) lecturers of construction technology civil engineering (CTCE) of vocational college using the standard model of competency requirement based on grade of lecturer and years of teaching experience. The data were analyzed using the SPSS Version 20.0 software, which involved descriptive statistical method, mean, and standard deviation. Data collection for the assessment phase involves construction technology lecturers from 45 vocational colleges in all the states in Peninsular Malaysia. The respondents of the study were 304 lecturers who taught CTCE courses in vocational colleges from 14 states, namely Johor, Sarawak, and Federal Territory (Kuala Lumpur and Labuan). Finding shows that the professional general competency level of TVET CTCE vocational college lecturers based on years of teaching experience is high with satisfactory interpretation. It also shows that the level of professional competency of TVET CTCE lecturer of vocational college based on grade of the post is high, whereas the level of entrepreneurship skill competency as a whole is at moderate level. There was a slight decrease in the proficiency level profile of the CTCE lecturer who had more than 15 years of experience compared with those with teaching experience of 15 years or less. There found positive relationships between the dimensions of professionalism and the generic skills. The findings of the study will help the Ministry of Education in particular public or private institutions of higher learning in preparing TVET lecturers to become specialized, highly skilled, competent, and efficient in civil engineering courses in the attempt to strengthen the teaching profession, especially in technical and vocational education, which is in line with the aspirations of the 21st-century education. © The Author(s) 2019.